29‐2: Invited Paper: An Ultra‐Low Power FFS LCD Using Zero‐Anchoring Interface. Issue 1 (28th June 2022) - Asagi, Hiroaki; Murata, Koji; Matsumoto, Kazuhito; Nishihara, Yusuke; Hashimoto, Yoshito; Minoura, Kiyoshi
Abstract : Using a novel zero‐anchoring (ZA) interface, we have realized an ultra‐low power consumption FFS LCD with low voltage drive and higher transmittance than FFS using negative liquid crystal. In addition, we have improved the response time, image sticking and other optical performance, which have been issues for zero anchoring FFS, by developing the alignment layer materials and the optimum liquid crystal materials. It is expected to be adopted in applications requiring low power consumption in the future.